RAMADHAN, EID UL FITR, AND INFLATION: LESSON FROM INDONESIAN SUBNATIONAL DATA - Samsubar Saleh; Dyah Titis Kusuma Wardani; Madha Adi Ivantri (Jurnal Ekonomi & Studi Pembangunan, 2019)
Inflation has always been being seen as one of the most important macroeconomic variables in modern economies. Every year, media especially in Muslim countries has constantly reported that inflation rates increase during the Islamic holy month of Ramadhan and Eid Ul Fitr. Remarkably, there has been hitherto almost no serious study focusing on the empirical relationship between Ramadhan, Eid Ul Fitr and inflation. This research aims to examine empirically whether Ramadhan and Eid Ul Fitr have a systematic effect on inflation. This research uses regression analysis technique and involves data from 66 local economies in Indonesia between January 2000 and December 2017. The finding of this paper is Ramadhan and Eid Ul Fitr have a positive effect on inflation. The possible reasons for explaining the results is the high of public demand. To overcome inflation in Indonesia not only from the role of government in controlling inflation rate, but also the role of Muslims community in controlling consumption.